Comprehensive Identification of Chemical Fingerprint and Screening of Potential Quality Markers of Aloe vera (L.) Burm. f. from Different Geographical Origins via Ultra-High-Performance Liquid Chromatography Hyphenated with Quadrupole–Orbitrap-High-Resolution Mass Spectrometry Combined with Chemometrics. (9th March 2023) - Yan, Yahui; Abdulla, Rahima; Ma, Qingling; Aisa, Haji Akber
Abstract: An integrated strategy was developed for the systematic chemical fingerprint and chemometrics analysis for the quality assessment of Aloe vera (L.) Burm. f. The ultra-performance liquid chromatography fingerprint was established, and all common peaks were tentatively identified by using ultra-high-performance liquid chromatography hyphenated with quadrupole–orbitrap-high-resolution mass spectrometry. Afterwards, the datasets of common peaks were subjected to hierarchical cluster analysis, principal component analysis and partial least squares discriminant analysis to holistically compare the differences. The results revealed that the samples were predicted to fall into four clusters, which were related to four different geographical locations. Using the proposed strategy, aloesin, aloin A, aloin B, aloeresin D and 7- O -methylaloeresin A were rapidly determined to be the potential characteristic quality markers. Finally, five screened compounds in 20 batches of samples were simultaneously quantified, and their total contents were ranked as follows: Sichuan province > Hainan province > Guangdong province > Guangxi province, which suggests that geographical origins may be an important factor affecting the quality of A. vera (L.) Burm. f. This new strategy can not only be used to explore possibly the latent active substance candidates for pharmacodynamic studies, but it is also an efficient analytical strategy for other complex traditional Chinese medicine systems.